Determinants of University Students' Reading Literacy: The Roles of Digital Literacy, Academic Engagement, and Demographic Factors - Muhammad Iqbal; Bambang Robiin; Agus Jayadi; Rila Hardiansyah; Ahmad Muslim (The Indonesian Institute of Science and Technology Research, 2026)
Reading literacy is a fundamental competency for university students, particularly those in teacher education programs who will be responsible for developing literacy skills in future generations. This study investigated the determinants of reading literacy among 185 university students at the Faculty of Education and Psychology, Universitas Pendidikan Mandalika, Indonesia. Using a quantitative explanatory survey design, hierarchical multiple regression analysis was employed to examine the effects of demographic variables (gender, GPA, semester, and study program), academic engagement, and digital literacy on reading literacy. The results revealed that demographic variables collectively explained 12.4% of the variance in reading literacy (p = .001), with gender and study program emerging as significant predictors. The addition of digital literacy and academic engagement increased the explained variance by 5.5% (p = .003), with digital literacy being the strongest predictor (β = .247, p = .001). Interestingly, academic engagement did not significantly predict reading literacy when controlling for other variables. Moderation analysis indicated that demographic variables did not moderate the relationships between digital literacy or academic engagement and reading literacy (ΔR² = .021, p = .615), suggesting that the benefits of digital literacy on reading skills is consistent across demographic groups. These findings highlight the importance of integrating digital literacy development into teacher education curricula and suggest that interventions to enhance reading literacy should prioritize digital competencies regardless of students' demographic backgrounds.